Tuning the Self‐Assembly of Oligothiophenes on Chemical Vapor Deposition Graphene: Effect of Functional Group, Solvent, and Substrate. Issue 7 (18th May 2014) - Sun, Xiuling; Mu, Youbing; Zhang, Jia; Wang, Xiaona; Hu, Pingan; Wan, Xiaobo; Guo, Zongxia; Lei, Shengbin
Abstract Tuning and characterizing the interfacial structure of organic semiconductors on graphene is essential for graphene‐based devices. Regulation of the supramolecular assembling structure of oligothiophenes on graphene by changing functional groups attached to the backbone of oligothiophenes is described and the assembling behavior is compared with that on the basal plane of highly oriented pyrolytic graphite. It reveals that terminal functional groups attached to the conjugated backbone of oligothiophene can entirely change the assembling structures. Significant solvent and substrate effects have also been confirmed by comparing the assembling structures of oligothiophenes deposited from tetrahydrofuran, 1, 2, 4‐trichlorobenzene, and octanoic acid onto graphene and graphite.